The Influence of Leadership Style and Competence Through Work Motivation on Employee Performance at the Housing and Settlement Areas Service of Tanjung Jabung Timur Regency - Oktarini Oktarini; Hapzi Ali; Maya Maria (Dinasti Publisher, 2025)
This study aims to analyze the influence of leadership style and competence on employee performance with work motivation as an intervening variable at the Housing and Settlement Areas Agency of East Tanjung Jabung Regency. The background of this study is based on the phenomenon of declining employee performance indicators in recent years, which indicates the need for a study of the determinants of apparatus performance. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 57 employees. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results show that leadership style, competence, and work motivation have a positive and significant effect on employee performance. In addition, leadership style and competence also have a positive and significant effect on work motivation. Testing of intervening variables indicates that work motivation is able to mediate some of the influence of leadership style and competence on performance, although the direct effect is more dominant than the indirect effect. These findings emphasize the importance of the role of effective leadership and the suitability of employee competence in improving the performance of public organizations.